Hubungan Status Gizi dengan Hasil Belajar Siswa - Tarigan, Beltasar; Hidayat, Teten; Angga Lardika, Rola (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
This study aimed to determine the relationship between student nutritional status and learning outcomes, especially physical education in junior high schools in Bandung City, West Java Province. The research used is correlational. The population of this study amounted to 98,289 students. Sampling using a simple random sampling technique. The research sample amounted to 1870 students. This study uses primary data that is obtained from the measurement of the nutritional status of students and secondary data from physical education teachers in Bandung. The data collection tool measures nutritional status based on body mass index and learning outcomes with student scores from teachers. The data were analyzed by correlational statistics through a computerized process using the SPSS program. From the study results, it can be concluded that there is no significant relationship between nutritional status and learning outcomes for both male and female students in junior high school. Further research by examining other factors related to BMI and other factors related to learning outcomes, such as socioeconomic and family factors.